Genomic Surveillance of SARS-CoV-2: Data Analysis and Assessment of Tunisian Strategy from January 2021 to February 2022 - Arwa Neffati; Mouna Safer; Wissal Kalai; Aicha Hechaichi; Sonia Dhaouadi; Hajer Letaief; Chaima Aichouch; Leila Bouabid; Sondes Darouiche; Nawel El Mili; Henda Triki; Ilhem Boutiba; et al. (Epidemiologia, 2024)
Due to the emergence of the SARS-CoV-2 B.1.1.7 (Alpha) variant in the UK in 2020 and its risk of increased transmission, the Ministry of Health in Tunisia implemented a sequencing surveillance strategy for SARS-CoV-2. The aim of this study was to analyze SARS-CoV-2 genomic surveillance data in Tunisia (January 2021–February 2022) and to assess the implementation of the sequencing strategy for SARS-CoV-2 in accordance with national recommendations and the guidance for SARS-CoV-2 genomic surveillance for public health goals. A descriptive study of all sequenced RT-PCR samples sequenced (January 2021–February2022). An internal audit was also done to assess the compliance against standards covering national recommendations and the Guidance for SARS-CoV-2 genomic surveillance for public health goals. A total of 12 simple or composite requirements related to the following areas were included in the audit standards: sampling (one requirements); data collection/analysis (six requirements); partnership (one requirement); and ethical considerations (one requirement). A total of 4819 samples were sent to laboratories and 4278 samples were sequenced. A total of 3648 samples were classified. Positive variants of concern (VOC) samples were 80.92%, differentiated as follows: Alpha, 40.24%; Beta, 0.24%; Gamma, 0.03%; Delta, 45.26%; and Omicron, 14.19%. Three principal phases of VOCs per ISO-week were shown: Alpha 3/2021–25/2021; Delta 26/2021–2/2022; and Omicron 3/2022–6/2022. Levels of compliance were identified; from a total of 12 requirements, 7 were considered as “not met”, 4 as “partially met”, and 1 as “fully met” but including not totally achieved objectives. In conclusion, the internal audit of the national SARS-CoV-2 sequencing strategy revealed an overall “not met” level of compliance. The results offered a trigger to collaborate with all stakeholders to develop a surveillance strategy for early detection and response to outbreaks caused by VOCs.